Cloud Superstream Sustainability in the cloud - Currie, Anne; Hsu, Sarah; Bergman, Sara; Hussain, Asim; Karroqe, Mary; Gibson, Zinnia; Maheshwar, Sohan; Goldenring, Kate (O'Reilly Media, Inc., 2023)
Climate disaster is looming, and the day of reckoning is here. Businesses can no longer afford to ignore their part in the changing climate. Environmental sustainability is now a top strategic priority for IT teams, and for good reason. Greener computing practices are not only good for the planet but can also be a driver of cost-efficiency and innovation. The leading cloud providers have all pledged to decarbonize their data centers and use renewable energy, but how can organizations and individual contributors take part and hold them accountable? What are the impacts of your cloud use? And how can your organization be more efficient? Join leading experts for a half-day of sessions that will answer these tough questions and set you on the path to greener cloud computing. The need for greener practices (like smart infrastructure) is urgent; this Superstream event will help you start implementing them. What you'll learn and how you can apply it Understand the environmental implications of software development and cloud operations and why it is so urgent to adopt more sustainable practices Learn how to reduce software emissions, optimize cloud resources, and measure your carbon impact using a variety of protocols, tools, and best practices Learn how to communicate with colleagues and leaders about green computing initiatives and become an advocate for sustainability in your organization This live event is for you because... You're a software developer or engineer working in the cloud and you want to build more responsible and efficient applications. You're a cloud architect, operations manager, or engineering leader responsible for helping your organization achieve its sustainability goals. You care about the planet and want to be a part of the solution in your organization. Recommended follow-up: Read Building Green Software (early release book) Watch Infrastructure & Ops Hour with Sam Newman: Cloud Providers and Sustainability with Anne Currie (video) Listen to Understanding Corporate Sustainability (audiobook).
Online resource; title from title details screen (O'Reilly, viewed Decenber 5, 2023)
Keywords: Cloud computing; Instructional films; Nonfiction films; Internet videos